Real-time data collection and analysis of user experience in video games - TUNCALI YAMAN, TUTKU; ERDEN, AYDIN; GÜNEŞ, BATIKAAN (My University, 2022)
In this study, a system proposal has been made that will measure the real-time experience of the player in video games and create process maps specific to certain user types, which will enable various changes to increase the user experience during gameplay. Among the components of the system, a multidimensional data set will be obtained from both the eye tracking and facial expressions of the user, and then processed with a deep learning model. To do so the real user experience and mode will be measured, on the other hand, a process mining model will be created by taking the logs during the game and the outputs of the deep learning software. This model will be integrated into the game software and combined with the gameplay data of each player during the game, providing a special game experience to the user
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Yönetim Bilişim Sistemleri; Bilgisayar Bilimleri; Yazılım; Yazılım Mühendisliği; Mühendislik ve Teknoloji; Social Sciences and Humanities; Management; Management Information Systems; Computer Sciences; Software; Software Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Bilgisayar Bilimi; Ekonomi ve İş; BİLGİSAYAR BİLİMİ, YAZILIM MÜHENDİSLİĞİ; İŞLETME; YÖNETİM; Engineering, Computing & Technology (ENG); Social Sciences (SOC); COMPUTER SCIENCE; ECONOMICS & BUSINESS; COMPUTER SCIENCE, SOFTWARE ENGINEERING; BUSINESS; MANAGEMENT; Karar Bilimleri (çeşitli); Genel Karar Bilimleri; Bilgisayar Bilimi Uygulamaları; Bilgisayar Bilimi (çeşitli); Genel Bilgisayar Bilimi; Strateji ve Yönetim; Pazarlama; İşletme ve Uluslararası Yönetim; Genel İşletme, Yönetim ve Muhasebe; Fizik Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; Decision Sciences (miscellaneous); General Decision Sciences; Computer Science Applications; Computer Science (miscellaneous); General Computer Science; Strategy and Management; Marketing; Business and International Management; General Business, Management and Accounting; Physical Sciences; Social Sciences & Humanities